1998
DOI: 10.1007/s004170050144
|View full text |Cite
|
Sign up to set email alerts
|

Growth factors in cultured pterygium fibroblasts: immunohistochemical and ELISA analysis

Abstract: The strong immunoreactivity and the release of b-FGF in cultured fibroblasts of recurrent pterygia suggest that fibroblasts may play an important role in the recurrence of pterygium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
1
6

Year Published

2001
2001
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 20 publications
0
66
1
6
Order By: Relevance
“…2,3 Several environmental factors that may induce ocular inflammation and various cytokines have been reported to be involved in the development of pterygium. [4][5][6] However, the precise mechanism of pterygium pathogenesis is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Several environmental factors that may induce ocular inflammation and various cytokines have been reported to be involved in the development of pterygium. [4][5][6] However, the precise mechanism of pterygium pathogenesis is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…UV-mediated genetic trauma may also affect the expression of various cytokines, growth factors and growth factor receptors (6). The presence of such factors in pterygium has been evaluated in previous studies using various methods including immunohistochemistry and ELISA in cell cultures (12). This study focused on the evaluation of five growth factors (TGFB1, VEGFA, FGF, IGF1 and EGF), which had previously been shown to be individually affected in pterygium (6), and employed qRT-PCR to detect possible alterations in the expression of these factors in pterygium, compared with normal conjunctiva as well as potential clinical associations of molecular findings.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies that differentiated primary and recurrent pterygia reported that the levels of VEGF, basic fibroblast growth factor, and substance P were significantly higher in recurrent disease (9) . Markers for vascular endothelial cells such as CD31+ are increased in pterygium, which supports angiogenesis (10) .…”
Section: Introductionmentioning
confidence: 99%